Wireless power transfer system design for electric vehicle dynamic charging application - Nguyen Thi Diep; Nguyen Kien Trung; Tran Trong Minh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper proposes and demonstrates a wireless power transfer system design for electric vehicle dynamic charging applications. The dynamic wireless charging (DWC) lane is designed for modularly. Each module has three shorttrack transmitter coils that are placed closely together and connected to a single inverter to reduce the number of inverters. The magnetic coupler design is analyzed and optimized by finite element analysis (FEA) to reduce the output power variation during dynamic charging. The LCC compensation circuit is designed according to the optimal load value to obtain maximum efficiency. The SIC devices are used to improve the efficiency of the high-frequency resonant inverter. A 1.5 kW dynamic charging system prototype is constructed. Experimental results show that the output power variation of 9.5% and the average efficiency of 89.5% are obtained in the moving condition.